2014
DOI: 10.5398/medpet.2014.37.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Body Resistance and Productive Performances of Crossbred Local Chicken Fed Inulin of Dahlia Tubers

Abstract: The research was aimed to examine the role of inulin as a prebiotic derived from dahlia flower tuber in the form of powder and extract as a prebiotic on body immunity of crossbred local chicken. The research was assigned in a completely randomized design with 7 treatments and 4 replications (10 birds each). The treatments applied were T0:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
3
11
0
3
Order By: Relevance
“…The present results showed that broiler chickens given diet supplemented with GEPT at all levels (Table 3) had lower H/L ratio than control treatment. The result was similar to the report of Fajrih et al (2014) that the inclusion of inulin up to 1.17% lowered H/L ratio than control. The lower H/L ratio induced by GEPT inclusion indicated that the bird was in a favorable condition or suffered low stress (Hosseini et al, 2016).…”
Section: Body Resistance and Growth Performancesupporting
confidence: 91%
See 1 more Smart Citation
“…The present results showed that broiler chickens given diet supplemented with GEPT at all levels (Table 3) had lower H/L ratio than control treatment. The result was similar to the report of Fajrih et al (2014) that the inclusion of inulin up to 1.17% lowered H/L ratio than control. The lower H/L ratio induced by GEPT inclusion indicated that the bird was in a favorable condition or suffered low stress (Hosseini et al, 2016).…”
Section: Body Resistance and Growth Performancesupporting
confidence: 91%
“…However, the present result was different from those previously reported as described above. Also, it was inconsistent when compared to Fajrih et al (2014) that crossbred local chickens given control diet, without prebiotic inulin of dahlia tuber, had higher spleen weight. The higher spleen weight could be associated with the infected state of pathogenic bacteria and stimulated the spleen to work harder which followed by the increased weight and size.…”
Section: Body Resistance and Growth Performancementioning
confidence: 97%
“…This result is in agreement with the report of Krismiyanto et al (2014) that the increased lactic acid bacteria (LAB) population was due to the feeding effect of inulin derived from dahlia tuber which can intensely fermented by endogenous beneficial bacteria. Thus, the drecreased fat meat content and cholesterol concentration found in the present study can be associated with the increase in bile salt hydrolase (BSH) enzyme produced by the enhanced growth of LAB (Fajrih et al, 2014). This biochemical mechanism will be discussed further in the following paragraph, especially for cholesterol metabolism.…”
Section: Level Of Dahlia Tuber Powdermentioning
confidence: 54%
“…Heterophyl and lymphocyte (H/L) ratio can be used as an indicator of health or body resistance status which was caused by feeding inulin source in the form of either powder or extract form. The value of H/L ratio was categorized normal (0.5 in average) and lower when compared to control/T0 (0.69) (Fajrih et al, 2014). According to Kusnadi (2008), H/L ratio was the indication of discomfort condition of the poultry, the higher the ratio, the higher the level of discomfort.…”
Section: Resultsmentioning
confidence: 99%
“…One species of plants in Indonesia which can be used as the source of inulin (prebiotic) is Dahlia variabilis tuber. Dahlia tuber powder contains inulin with the range of 69.50-75.48% (Fajrih et al, 2014). Inulin functions as a probiotic because it becomes a food substrate component for beneficial microbes in the small intestine.…”
Section: Introductionmentioning
confidence: 99%